Reconstruction of the Muhammadiyah Educational System in Social Change - Suprapto, Suprapto; Hadi, M Faziurrahman; Jayadi, Mahsun (Jurnal Pendidikan Edutama, 2024)
This research aims to reveal the role of Muhammadiyah education in social transformation that influences people’s lives. The approach used is literature study. Capitalism in the educational context is often associated with the exploitation of business opportunities, whic often leads to unethical practices, such as the use of educational funds for personal gain or institutional interests. The aim of this research is to find a solution to overcome the problem of capitalization in education, which has had an impact on the high dropout rate among students. economic empowwerment efforts are important in this context, where education funding is often subsidized to overcome the challenge of high costs in providing education.